The Negative Impacts of the Grammar-Translation Method on Second Language Acquisition in Tiji Secondary Schools (مجلة العلوم الشاملة, 2025)
This research investigates the detrimental impact of the Grammar-Translation Method on second language acquisition among students at Tiji Secondary Schools. Despite its longstanding presence in language education, this method has been widely criticized due to its emphasis on grammar instruction and translation exercises, often at the expense of developing listening and speaking abilities and skills that are essential for linguistic fluency and communicative competence. Employing a qualitative research design, the study gathers data through interviews with teachers. The results consistently reveal that this method constrains learners’ oral and aural proficiency, promoting rote memorization over meaningful language use and personal development. Consequently, the study advocates for the adoption of more communicative and learner-centered pedagogical approaches that better support language acquisition and enhance students’ academic outcomes.